Prevalence and intensity of ectoparasites in giant freshwater prawn: Implications for aquaculture - Khasani, Ikhsan; Pamungkas, Wahyu; Nisaa, Khairun; Anggraeni, Agustin (Iraqi journal of veterinary sciences, 2026)
The giant freshwater prawn (GFP) is highly susceptible to ectoparasite infestations, particularly under suboptimal management conditions. This study investigates the prevalence and intensity of ectoparasites on various prawn body parts, including the gills, body surface, swimming legs, and walking legs. A total of 180 prawns were sampled from the GFP culture ponds located in the Subang region of West Java, Indonesia. These samples were then analyzed microscopically. Identified ectoparasites included protozoans (Epistylis sp., Zoothamnium sp., Vorticella sp.) and Temnocephala sp. The prevalence and intensity levels were as follows: Temnocephala sp. (100%; 907 individuals/prawn), Zoothamnium sp. (27%; 35 individuals/prawn), Vorticella sp. (27%; 26 individuals/prawn), and Epistylis sp. (29%; 4 individuals/prawn). The gills exhibited the highest prevalence (100%) and intensity (550 individuals/prawn), severely impacting respiration and increasing mortality risk. These findings highlight the urgent need for effective parasite management strategies in GFP aquaculture to minimize economic losses and enhance sustainability.